Heat stress tolerance in Indonesian cattle: Genetic basis, physiological mechanisms, and reproductive performance (Review Article) - Sari, Dinda Ayu Permata; Prima, Ari; Mustofa, Fatmawati (Journal of Advanced Veterinary Research, 2026)
Heat stress is one of the main environmental factors affecting the productivity and reproductive performance of cattle in tropical regions. Local cattle in Indonesia and other tropical countries have varying levels of adaptation to high temperature and humidity conditions, which are reflected in physiological responses and molecular mechanisms. Physiological indicators such as respiratory rate, rectal temperature, and heart rate, combined with reproductive parameters such as calving interval, days open, and conception rate, are often used to evaluate the impact of heat stress. At the molecular level, a number of candidate genes have been identified as playing a role in the heat stress response, including HSP70, ATP1A1, BCKDHA, HSPB6 and MYO1A, which are associated with cellular protection, antioxidant, and stress hormone regulation mechanisms. This article reviews the physiological and genetic basis of heat stress tolerance in tropical local cattle, as well as its implications for maternal reproductive performance. The review was undertaken to integrate existing knowledge and provide a comprehensive understanding of the interaction between genetic and physiological factors under conditions of heat stress. The expected outcome is the identification of potential biomarkers that can be applied in cattle breeding and management. This understanding is expected to support genetic marker-based local cattle breeding programmes, in order to improve heat stress resistance while maintaining reproductive productivity in tropical regions. The findings ultimately serve as a scientific foundation for the formulation of policies and the development of sustainable livestock strategies in tropical countries.